Influence of Learning PAI on Ramadan Fasting Experience of SMPN 176 Students Cengkareng, Jakarta Barat - Zubairi, Zubairi; Abnisa, Almaydza Pratama (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The study entitled